TEMA: GASTRONOMÍA TRADICIONAL Y SU INCIDENCIA EN EL DESARROLLO TURÍSTICO DEL CANTÓN QUEVEDO, PROVINCIA DE LOS RIOS AÑO 2022. - Morales Pincay, Susan Melissa (2022)
The present investigation is carried out with the objective of knowing the contribution of traditional gastronomy for the tourist development of the canton. Currently, Quevedo receives a large number of tourists from various places who come to learn about its natural environment, tradition and culture. It is clear that gastronomy is an important part of the tourist attractions of the canton, the taste and good price influence its high demand, on which many businesses in the area depend, offering a variety of typical dishes of consumer preferences. The design of the informative brochure will influence the tourist, economic and social development of the city, becoming a potential site that brings together a great gastronomic variety and quality service for visitors to the canton.